术后放疗在期Ⅰ/Ⅱ期/Ⅲ期胸腺肿瘤中的作用——ChART回顾性数据库研究结果 (Zhongguo Fei Ai Za Zhi, 2016)
BACKGROUND AND OBJECTIVE: Postoperative radiotherapy (PORT) for thymic tumor is still controversial. The object of the study is to evaluate the role of PORT for stage Ⅰ/Ⅱ/Ⅲ thymic tumor. METHODS: The database of Chinese Alliance of Research for Thymomas (ChART) was retrieved for patients with stage Ⅰ/Ⅱ/Ⅲ thymic tumor who underwent surgical therapy without neoajuvant therapy between 1994 and 2012. Univariate and multivariate survival analyses were performed. Cox proportional hazard model was used to determine the hazard ratio for death. RESULTS: 1, 546 stage Ⅰ/Ⅱ/Ⅲ patients were identifed from ChART database. Among these patients, 649 (41.98%) underwent PORT. PORT was associated with gender, histologic type (World Health Organization, WHO), surgical extent, complete resection, Masaoka stage and adjuvant chemotherapy. The 5-yr and 10-yr overall survival (OS) rates and disease-free survival (DFS) rate for patients underwent surgery followed by PORT were 90% and 80%, 81% and 63%, comparing with 96% and 95%, 92% and 90% for patients underwent surgery alone (P=0.001, P < 0.001) respectively. In univariate analysis, age, histologic type (WHO), Masaoka stage, completeness of resection, and PORT were associated with OS. Multivariable analysis showed that histologic type (WHO)(P=0.001), Masaoka stage (P=0.029) and completeness of resection (P=0.003) were independently prognostic factors of OS. In univariate analysis, gender, myasthenia gravis, histologic type (WHO), Masaoka stage, surgical approach, PORT and completeness of resection were associated with DFS. Multivariable analysis showed that histologic type (WHO) (P < 0.001), Masaoka stage (P=0.005) and completeness of resection (P=0.006) were independently prognostic factors of DFS. Subgroup analysis showed that patients with incomplete resection underwent PORT achieved the beter OS and DFS (P=0.010, 0.017, respectively). However, patients with complete resection underwent PORT had the worse OS and DFS (P < 0.001, P < 0.001, respectively). CONCLUSION: The current retrospective study indicated that PORT afer incomplete resection could improve OS and DFS for patients with stage Ⅰ/Ⅱ/Ⅲ thymic tumor. But for those afer complete resection, PORT may not help improve prognosis on the whole.